Application of a screening test for antibody the hepatitis B core antigen. Issue 8 (August 1977) - Cohen, B J; Cossart, Y E
Abstract : Hepatitis B core antigen (HBcAg) was prepared from human liver tissue and used in an immunoelectro-osmophoresis screening test to detect antibody to HBcAg (anti-HBc) in patients with evidence of liver disease and in blood donors. With the exception of two immunosuppressed HBsAg carriers, anti-HBc was found in all cases of hepatitis B infection even when HBsAg was detectable only by radioimmunoassay. Non-specific reactions were observed in 'non-B' hepatitis but, in spite of this problem, antib-HBc screening was considered a useful addition to routine tests in the clinical hepatitis laboratory.